Molecular and Functional Characterization and Expression Analysis of a Delta6 Fatty Acyl Desaturase cDNA of European Sea Bass (Dicentrarchus labrax L.) - Gonzalez-Rovira, Almudena; Mourente, Gabriel; Zheng, Xiaozhong; Tocher, Douglas R; Pendon, Carlos (Aquaculture, 2009)
The extent to which fish species can produce highly unsaturated fatty acids (HUFA) from C18 fatty acids varies with their complement of fatty acyl desaturase (FAD) enzymes. Marine fish are unable to produce HUFA at a significant rate due to apparent deficiencies in one or more enzymatic steps in the desaturation/ elongation pathway. It is not known if this is due to a lack of the genes or to tight regulation of the enzymatic activity in some of the transformation steps. In the present study, we report molecular cloning, cDNA, protein and functional analysis of a Δ6 FAD of European sea bass (Dicentrarchus labrax L.), and describe its tissue expression and nutritional regulation. An FAD cDNA contig sequence from brain tissue of sea bass was obtained by gene walking, and full-length cDNA was obtained by amplification using 5′end forward and 3′ end reversed primers. The full length of the sea bass FAD cDNA was 2089 bp, which included a 5′-UTR (untranslated region) of 267 bp, a 3′-UTR of 484 bp and an open reading frame (ORF) of 1338 bp, which specified a protein of 445 amino acids. The mRNA size, estimated by northern blot analysis was 2.1 kb, consistent with the cDNA. Transient expression of Δ6-FAD-EGFP in HeLa cells showed the protein compartmentalized to the endoplasmic reticulum. Functional expression in yeast showed the sea bass cDNA encoded a unifunctional Δ6 FAD enzyme. The sea bass FAD was more active towards 18:3n-3 with 14.5% being converted to 18:4n-3 compared to 5.6% of 18:2n-6 converted to 18:3n-6. Expression of the Δ6 FAD gene in the sea bass tissues showed a rank order of heart, brain, ovary, kidney, adipose tissue and liver as determined by RT-qPCR. Nutritional regulation of gene expression was studied. Diets containing partial substitution of fish oil with rapeseed or linseed oils induced up-regulation of the Δ6 FAD gene; whereas, a diet containing olive oil did not influence the expression. Similarly, when fish oil was partially replaced by blends of vegetable oils, one increased expression and one ...